Assessment of EMF Exposure Induced by Wireless Cellular Phones in Various Usage Scenarios in France - Jiang Liu; Yarui Zhang; Wassim Ben Chikha; Shanshan Wang; Theodoros Samaras; Ourouk Jawad; Lamine Ourak; Emmanuelle Conil; Joe Wiart (IEEE Access, 2025)
With the ever-increasing demand for high-speed and low-latency wireless communications, new generation of base stations, i.e., the fifth generation (5G), has been deployed recently. However, this deployment has raised growing concerns regarding the potential public health implications associated with exposure to radio-frequency electromagnetic fields (RF-EMF). According to the type of sources, RF-EMF exposure can be categorized into uplink (device-to-base station) and downlink (base station-to-device) transmissions. In this paper, we aim to analyze uplink exposure induced by mobile devices operating on 5G and previous generations. A total of 380 measurement points are selected for evaluating three types of services, i.e., voice call, video call, file uploading, in the Greater Paris region. Data collected from those measurements cover technologies in 2G, 3G, 4G, and 5G, where 5G refers to non-standalone (NSA) in the current paper. We compare the average transmitted (TX) power, throughput, connection duration, and energy utilization efficiency for different services and frequency bands. To assess the impact of 5G, we used NEMO system from Keysight to conduct measurements with the 5G functionality enabled and disabled, respectively. The data analysis revealed that mobile phones emit higher power during data-intensive services. Additionally, mobile phones operating on 5G emit lower TX power than 4G. Furthermore, the UL exposure level also depends on the duration of emission. For a given file size to upload, the duration depends on the throughput. Consequently, we also investigated the emitted energy consumption per bit transmitted, referred to as radiated energy per bit transmitted (REBT). The comparison reveals that REBT in file uploading is 9.65 mJ/Mb for 4G and 5.1 mJ/Mb for 5G, indicating a significant decrease in radiated energy consumption with the adoption of 5G technology. This research enhances our understanding of uplink RF-EMF exposure associated with 5G and provides crucial insights for public health risk assessments.